On the transitivity and primitivity of permutation groups of degree 4p constructed via wreath products using numerical approach - Johnson*, B. O.; Hamma†, S.; Adamu†, M. S. (International Journal of Mathematical Analysis and Modelling, 2023)
Let p be an odd prime number and G a finite permutation group of degree 4p generated via wreath products of pairs of permutation groups. In this work, a group concept, namely isomorphism, is applied to discuss the transitivity and primitivity of G using numerical approach. The computational group theory (GAP) is applied to enhance and validate our work.